Inhibition of PDGF-BB by Factor VII-activating protease (FSAP) is neutralized by protease nexin-1, and the FSAP–inhibitor complexes are internalized via LRP - Muhl, Lars (Portland Press Ltd., 2007)
FSAP (Factor VII-activating protease) can inhibit neointima formation and VSMC (vascular smooth-muscle cell) proliferation by cleavage of PDGF-BB (platelet-derived growth factor-BB). Negatively charged polyanions lead to autoactivation of the FSAP, but no information is available concerning the potential regulation of FSAP activity and its metabolism in the vessel wall. In the present study, we demonstrate that the enzymatic activity of FSAP can be inhibited by the serine protease inhibitor, PN-1 (protease nexin-1), that is found in the vasculature. This leads to the loss of the inhibitory effect of FSAP on PDGF-BB-mediated DNA synthesis and mitogen-activated protein kinase phosphorylation in VSMCs. The FSAP–PN-1 complexes bind to the LRP (low-density lipoprotein receptor-related protein) and are subsequently internalized. This binding is inhibited by receptor-associated protein, an antagonist of LRP, as well as heparin. While PDGFβR (PDGFβ receptor) is internalized by an LRP-dependent mechanism after stimulation of cells by PDGF-BB, the FSAP–PN-1 complex neither influenced PDGF-BB-mediated phosphorylation of PDGFβR nor its internalization via LRP. Hence, PN-1 inhibits the enzymatic activity of FSAP and neutralizes its effect on PDGF-BB-mediated VSMC proliferation. The FSAP–inhibitor complexes are internalized via LRP without influencing the PDGF-BB signal transduction pathway.